THE STUDY OF PROSPECTS FOR THE DEVELOPMENT OF PLATINUM GROUP MINERALS IN THE DEPOSITS OF UZBEKISTAN (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Currently, the world demand is high for rare metals and they are not always found in sufficient compositions in ores as a result of detection methods are developed using satellite and processing of rare and rare metals of a particular polymetallic ore by satellite method. The proportion of the perfect physical and chemical properties of the metals of the platinum group makes it more relevant in the field of application and makes them irreplaceable metals in all areas of human activity.